Prevention and Control of Non-Communicable Diseases Hypertension With Community Empowerment In Bumiwangi Village In 2024 - Ramadhan, Adi Putra; Wulandari, Gina; Sutandi, Dede; Winengsih; Nurhayati, Eka; Salma, Tania (Universitas INABA, 2025)
Hypertension is a non-communicable disease that is a public health challenge in Indonesia, including in Bumiwangi Village. Low public awareness about the prevention and management of hypertension increases the risk of serious complications. This community service program aims to empower health cadres through training and education for the community on early detection and control of hypertension. The methods used include situation analysis, interviews, observations, problem identification, and interventions in the form of counselling and training of health cadres using the Integrated Service Post for Non-Communicable Diseases approach. This activity was carried out through collaboration between students, health workers, and village government. The evaluation results showed an increase in community knowledge and awareness of risk factors and better management of hypertension. This program is expected to increase community awareness and participation in efforts to prevent and manage hypertension in a sustainable manner